Knowledge Extraction dari Ulasan Aplikasi Gojek Menggunakan Analisis Sentimen Berbasis Aspek - Ken Ditha Tania; Anggun Ramadina (The Indonesian Journal of Computer Science, 2024)
Social media is transforming business, costumer relations, and behavior. The involvement of customers and impacts from social media affect product or service performance. This is because the consumer’s reviews are another important factor that builds brand image by showing product advantages and disadvantages. In order to enhance the business environment, the company may utilize this knowledge base to evaluate and enhance its business activities. The knowledge base approach might help the company or organization examine and extract information by using knowledge extraction. In this research, knowledge Extraction utilize Aspect-based Sentiment Analysis as the method for a better understanding and improving in analyze Gojek application reviews with Machine Learning approach by using Support Vector Machine (SVM).